Physical Performance During Soccer-7 Competition and Small-Sided Games in U12 Players - Sanchez-Sanchez, Javier (J Hum Kinet, 2019)
The aim of this study was to compare the activity profile (external loads) during soccer-7 competition versus 6 vs 6 small-sided games ( SSGs) in U12 players. Peak velocity (V(max)), total distance completed (DT), total distance relative to match duration, the percentage of DT in acceleration (%DAC) and in deceleration (%DEA), and the percentage of DT at different speeds were recorded. Six types of SSGs were randomly implemented: without pitch orientation-delimitation and with a limit of three ball-contacts per player (3TOU), with no limit of ball-contacts (MAN), with a greater number of players as internal-offensive wildcard players (2WI) or external-offensive wildcard players (4WE); and with pitch orientation-delimitation and crossing the rival goal-line while dribbling the ball without goalkeepers (INV) or using official goalkeepers (GKP). The physical demands of SSGs were compared with the average of two soccer-7 match plays. During soccer-7 match plays a lower %DAC and %DEA (p < 0.05) were observed compared to 2WI, 4WE, INV and GKP, and to INV and GKP, respectively. The V(max) and %HI were greater (p < 0.05) in soccer-7 match plays compared to all SSGs. In conclusion, the demands imposed on U12 players during different formats of SSGs differ from the soccer-7 match play demands, presenting a low stimulation of the actions performed at high-speed and an adequate simulation of acceleration-deceleration actions.